Pemanfaatan Ekstrak Kelopak Bunga Rosella (Hibiscus Sabdariffa Linn.) untuk Meningkatkan Kadar Hemoglobin dan Hematokrit Remaja Putri Penderita Anemia - Luluk Handayani; Sri Sumarni; Donny Kristanto Mulyantoro (JURNAL ILMU KEFARMASIAN INDONESIA, 2022)
This research aims to prove the provision beneﬁts of Rosella (Hibiscus sabdariﬀa Linn.) calyx extract to increase hemoglobin and hematocrit levels in female adolescents anemia. This research is a true experiment with a randomized pre-test and post-test control group design. Totals of samples were 40 female adolescents with anemia according to the inclusion and exclusion criteria divided by randomization sampling technique, consisting of two groups intervention groups and control groups. Data analysis used paired t-test statistical test to determine the diﬀerence between pretest and post-test each group and an independent t-test to determine the diﬀerence between the diﬀerent groups. The average diﬀerence in hemoglobin and hematocrit levels in the intervention group was higher than in the control group. The average diﬀerence in hemoglobin levels in the intervention group was 1.8 g/dL in and the control group was 0.9 g/dL, (p < 0.05), The diﬀerence in the average hematocrit level in the intervention group was 5.6% and the control group was 2.7% (p < 0.05). The researchers also found signiﬁcant statistics diﬀerences between hemoglobin and hematocrit levels of female adolescents from intervention and control groups s with a p-value < 0.05. The combination of Rosella (Hibiscus sabdariﬀa Linn.) calyx extract and Fe2+ tablet was eﬀective to increasing hemoglobin and hematocrit levels in female adolescents with anemia.